Enteroenteric and enterocutaneous fistula associated with recurrence of colon adenocarcinoma - Romero Sánchez, Jorge Adrián; Farell Rivas, Jorge; Ruiz-Funes Molina, Ana Paula (Cirugía del Uruguay, 2021)
42-year-old female patient with a history of right hemicolectomy due to colon cancer, with ileo-transverse anastomosis two years earlier. He came in for abdominal pain.